If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 2n + 3 = 4n + -6 Reorder the terms: 1 + 3 + 2n = 4n + -6 Combine like terms: 1 + 3 = 4 4 + 2n = 4n + -6 Reorder the terms: 4 + 2n = -6 + 4n Solving 4 + 2n = -6 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 4 + 2n + -4n = -6 + 4n + -4n Combine like terms: 2n + -4n = -2n 4 + -2n = -6 + 4n + -4n Combine like terms: 4n + -4n = 0 4 + -2n = -6 + 0 4 + -2n = -6 Add '-4' to each side of the equation. 4 + -4 + -2n = -6 + -4 Combine like terms: 4 + -4 = 0 0 + -2n = -6 + -4 -2n = -6 + -4 Combine like terms: -6 + -4 = -10 -2n = -10 Divide each side by '-2'. n = 5 Simplifying n = 5
| 26-x=8 | | (y)-8=32 | | 15x-2=180 | | 14x=35+7x | | 14x-18=12x+6 | | 4x-6y+9a= | | 7x+5(x-1)=12x-5 | | 3x^2+2x-4x=-2 | | 3x+4=3(x-7) | | 3y+4.9=2.6 | | 30-3*x=3 | | 2(4x-16)=8(x-4) | | 1.5y-1y=4+.5y | | 20-4x=x | | 40-4v=v | | f(x+7)=6x-6 | | 48+2y=8y | | 5=5(x+6) | | f(x+7)=6x-y | | 14-4v=3v | | -20=2(x-9) | | (10x^3y)x(2xy^6)= | | ln(x)+ln(2x^2+5)=0 | | f(-6)=6x-6 | | 1568=28lh | | 4x+6-2(2x+3)=3(2x-3) | | -56=8(x-8) | | 5t+1whent=-1 | | 0.5(4-6x)=8x-3(4x+6) | | B-z=b+hx | | 6xy+2y^2-10y=0 | | (7+y)+a=a+7 |